2018
DOI: 10.29252/jbrms.5.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neonatal factors and involving with glucose-6-phosphate dehydrogenase deficiency (G6PD) and patients' outcome in Fars Province

Abstract: Introduction: Glucose-6-phosphate dehydrogenase deficiency (G6PD) or fauvism is the most common enzyme deficiency in human, so that 400 million people are living with this disease worldwide. This study aimed to investigate the role of some neonatal factors among newborns suffering from G6PD deficiency and neonatal outcomes associated with this disease. Materials and methods: In this study, two methods including case-control and retrospective cohort regarding some neonatal factors associated with G6PD deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…The lack of significant association between the mode of delivery of the newborns and G6PD deficiency in the present study is in line with those reported from Fars, Iran [40] and Egypt [41], while the lack of significant association of G6PD deficiency among newborns and prematurity is consistent with findings from Fars and Isfahan in Iran [40,42] and India [43]. Some studies suggest that premature infants can even have a higher G6PD activity compared to near term infants, and prematurity does not interfere with the diagnosis of G6PD deficiency [44,45].…”
Section: Tablessupporting
confidence: 92%
“…The lack of significant association between the mode of delivery of the newborns and G6PD deficiency in the present study is in line with those reported from Fars, Iran [40] and Egypt [41], while the lack of significant association of G6PD deficiency among newborns and prematurity is consistent with findings from Fars and Isfahan in Iran [40,42] and India [43]. Some studies suggest that premature infants can even have a higher G6PD activity compared to near term infants, and prematurity does not interfere with the diagnosis of G6PD deficiency [44,45].…”
Section: Tablessupporting
confidence: 92%
“…Trong khi đó, không có sự khác biệt có ý nghĩa thống kê khi khảo sát theo các đặc điểm tiền sử gia đình, tuổi thai khi sinh, trọng lượng khi sinh, thiếu máu. Nghiên cứu của Daliri ở Iran cũng cho thấy mối liên quan của thiếu enzyme G6PD với vàng da, nhưng không liên quan với tuổi thai khi sinh, trọng lượng khi sinh [16]. Nghiên cứu của chúng tôi ghi nhận có 82,98% trẻ thiếu enzyme G6PD có vàng da.…”
Section: Kết Quả Chẩn đOán Thiếu Enzyme G6pd Và Một Số đặC đIểm Lâm Sàngunclassified